Illustrated accounts of coccinellid predators of Maconellicoccus hirsutus (Green) (Hemiptera: Sternorrhyncha: Pseudococcidae) on mulberry in India, with description of a new species of Scymnus Kugelann (Coleoptera: Coccinellidae) from West Bengal - Poorani, J.; Lalitha, N. (Zootaxa, 2018)
The pink hibiscus mealybug, Maconellicoccus hirsutus (Green), is a major pest of mulberry (Morus alba L.), the sole host of the mulberry silkworm, Bombyx mori (L.), which is a source of livelihood to millions of sericulture farmers in India. Several predators, mainly Coccinellidae (Coleoptera), have been reported to feed on M. hirsutus on mulberry. Coccinellid predators of M. hirsutus collected on mulberry from different parts of India are illustrated here with brief diagnostic notes to facilitate their identification. An account of mycophagous species of coccinellids commonly found on mulberry and misreported as predators of mulberry pests is also given with illustrations. Scymnus (Pullus) latifolius sp. nov., a promising predator of M. hirsutus, hitherto misidentified and reported as Scymnus pallidicollis Mulsant, is described and illustrated from West Bengal, India, with detailed biological notes. Keiscymnus taiwanensis Yang & Wu, 1972 is reduced to a new junior synonym of Scymnus pallidicollis Mulsant, 1853 (syn. nov.). Illeis bielawskii Ghorpade, 1976 is found to be a valid species and removed from synonymy with I. bistigmosa Mulsant, 1850 (stat. rev.).